A Prototype of Web-Based Computer Skills Training Course for Al Quds Open University (QOU) - Al Kayyali, Zakaria Khali D. (2006)
E-Applications become the most important proverb in the modem electronic world, which depend on computer based system in many fields in the world. It help links people, systems and others resources making life easier and better. The purpose of this project is to develop a prototype of Web-based Training system for Al Quds Open University(QOU). This prototype used the Microsoft VB.Net and Microsoft SQL Server as Database. This project is important in order to make the training tasks easier than current way and to allow the QOU staff attending training courses anytime anywhere.